1999
DOI: 10.1016/s1071-5576(99)00004-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased neutrophil-endothelial adhesion induced by placental factors is mediated by platelet-activating factor in preeclampsia

Abstract: In preeclampsia, the placenta releases one or more factors promoting neutrophil-endothelial adhesion. The increased neutrophil-endothelial adhesion thereby induced is a PAF-mediated event. It is suggested that if preeclamptic placentas release toxic factors into the maternal circulation in vivo, these factors may contribute to the altered vascular endothelial cell function in preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…However, some insights into the possible identity of these factors are provided by previously published work. For example, it has been shown that the increased neutrophil-endothelial adhesion induced by placental factors is mediated by platelet-activating factor (10). Endothelial protease-activated receptors, protease thrombin, and trypsin have also been implicated in the endothelial dysfunction induced by placental factors (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some insights into the possible identity of these factors are provided by previously published work. For example, it has been shown that the increased neutrophil-endothelial adhesion induced by placental factors is mediated by platelet-activating factor (10). Endothelial protease-activated receptors, protease thrombin, and trypsin have also been implicated in the endothelial dysfunction induced by placental factors (12).…”
Section: Discussionmentioning
confidence: 99%
“…Placental conditioned medium was prepared as follows (10,12). Briefly, fresh placentas from normal and preeclamptic pregnancies were collected and processed immediately after delivery.…”
Section: Coculture Of Endothelial Cells With Trophoblastsmentioning
confidence: 99%
“…Preeclampsia is defined severe if one or more of the following criteria is present: maternal blood pressure ≥160/110 mmHg; proteinuria >3+ or >5 g/24 h; oliguria of less than 500 ml in 24 h; intrauterine growth restriction, and presence of persistent headache or visual disturbances. Preeclamptic placental conditioned medium was prepared as previously described [9,15,16]. Briefly, villous tissue, excluding basal plates and fetal membranes, was incubated with serum free Dulbecco's Modified Eagles Medium (DMEM, Sigma Chemical Inc., St Louis, MO) for 48 h. At the end of incubation, the culture medium was collected and stored at -70 °C until use.…”
Section: Preparation Of Placental Conditioned Mediummentioning
confidence: 99%
“…Placental conditioned media (CM) were prepared from villous tissue explant culture from the placentas of preeclamptic patients as previously described [29,30]. Briefly, placentas were obtained immediately after delivery from preeclamptic pregnancies.…”
Section: Conditioned Medium Preparationmentioning
confidence: 99%